V.F. Odoevsky : his life, times and milieu - Cornwell, Neil (Bloomsbury academic collections. History. European history., 2015)
Odoyevsky (1804-1869) was a leading writer, musicologist, popular educator and public servant in Russia, close to the major historical events of his period and acquainted with many of the leading personalities, from Pushkin to Glinka, to Turgenev, Tolstoy and Tchaikovsky, as well as Berlioz and Wagner. Based upon published and unpublished sources in Russia and the West, Cornwell paints a portrait of one of Russia's central figures, though little known in the West.